Examining the Relationship Between Principal Management and Teachers’ Pedagogical Competence - Paiman; Eva Farihah; Ahmad Ahdian Faizal (Journal of Educational Management Research, 2025)
This study aims to examine the extent to which principal management influences teachers’ pedagogical competence within a secondary school context. Employing a quantitative correlational design, data were collected from 15 teachers through structured questionnaires measuring four dimensions of principal management (planning, organizing, actuating, and controlling) and five indicators of pedagogical competence. The data were analyzed using descriptive statistics, normality testing, Pearson correlation, and simple linear regression in IBM SPSS Statistics 24. The findings reveal a strong positive and statistically significant relationship between principal management and teachers’ pedagogical competence (R = .745, R² = .555, p < .05), indicating that principal management explains 55.5% of the variance in pedagogical competence. The regression model (Ŷ = 48.98 + 0.59X) suggests that improvements in managerial practices are associated with meaningful gains in teachers’ instructional capacity. These results underscore the pivotal role of effective school leadership in enhancing instructional quality and highlight the importance of strengthening principals’ managerial and instructional leadership competencies to support sustainable teacher professional development.